LIBRARY CAFE SEBAGAI SUATU TREN POPULER GENERASI Z - Puspita, Ika Destina; Endarwati, Endarwati; Rahayuningsih, Yanti (Journal Competency of Business, 2025)
This study analyzes the popularity of the library cafe as a popular trend among Generation Z. The phenomenon is understood as a blend of literary culture and a modern lifestyle influenced by social media. Using a qualitative approach with a consumer needs theory framework, this research identifies the factors that drive Gen Z's preference for the place. The findings indicate that library cafes effectively fulfill four main needs of Gen Z: comfort, connectivity, aesthetics, and productivity. The need for comfort is met through a relaxed atmosphere and comfortable physical facilities. Connectivity, provided by strong Wi-Fi, transforms the space into a flexible "second office." The aesthetic aspect, reflected in its "Instagrammable" interior design, satisfies Gen Z's need to create and share visual content. Furthermore, library cafes facilitate productivity by creating an environment that supports focus and positive social stimulation. In conclusion, the popularity of the library cafe is not merely a passing trend but a manifestation of how Gen Z consumes public spaces. This concept successfully integrates functionality (studying and working) with experience (socializing and aesthetics), making it a relevant and successful business model for the digital generation.